Approaching disaster risk financing in a structured way - Radu, Diana (Publications Office of the European Union, 2024)
As the number and magnitude of climate-related disasters in the EU are increasing, the impact of these disasters on public finances also depends on the extent to which budgets and budget plans reflect fiscal risks from disasters. At the same time, as many of these disasters can no longer be considered exceptional events, dealing with the fiscal cost of disasters calls for an informed national disaster financing strategy, also as a way to enhance a country's climate fiscal resilience. This discussion paper presents a structured approach to Disaster Risk Financing (DRF) in the EU Member States and describes the key elements needed to better understand, plan for and manage the fiscal cost of disasters. The paper proposes a step-by-step approach to DRF, building on previous analysis on the main concepts and ways to reduce and limit the fiscal cost of disasters. Member States willing to develop a national approach to disaster risk financing can act under four pillars to understand: (1) the fiscal impact of disasters, (2) private sector risk ownership, (3) public sector disaster risk management and (4) institutional arrangements. The Member States would be able to locate themselves in one stage of development of DRF:
10.2765/10427
Keywords: Graue Literatur; natural disasters; disaster risk financing; risk transfer; fiscal risks; disaster losses; climate change; insurance; national budget; disaster risk reduction; natural disaster; financial risk; emergency aid; financial aid